2020
DOI: 10.3390/ma13153388
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature on the Fretting Wear Behavior of 2.25Cr-1Mo Tubes against Gr5C12 Rods

Abstract: In the heat exchangers of sodium-cooled fast reactors, sodium flow can cause the tubes to vibrate, resulting in fretting wear damage due to the contact between the tubes (2.25Cr-1Mo steel) and their support plate (Gr5C12 alloy). In this work, the effects of temperature on the fretting wear behavior of a 2.25Cr-1Mo heat transfer tube on a Gr5C12 alloy rod were studied. The results showed that the coefficient of friction (COF) and wear volume increased first and then decreased with the increase in temperature. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 44 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…The above articles and other similar reports have shown that the key to understanding the wear of these alloys lies in the friction process. In fact, fretting wear includes many mechanisms, including abrasive, adhesive, and corrosion wear, of which abrasive and adhesive wear will be produced during the friction process [5,6]. Vanossi et al [7] summarized research progress on tribological phenomena in recent years and noted that the actual origin of friction was at the atomic scale; thus, the study of friction at the atomic scale has become increasingly important.…”
Section: Introductionmentioning
confidence: 99%
“…The above articles and other similar reports have shown that the key to understanding the wear of these alloys lies in the friction process. In fact, fretting wear includes many mechanisms, including abrasive, adhesive, and corrosion wear, of which abrasive and adhesive wear will be produced during the friction process [5,6]. Vanossi et al [7] summarized research progress on tribological phenomena in recent years and noted that the actual origin of friction was at the atomic scale; thus, the study of friction at the atomic scale has become increasingly important.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some researchers are keen on the wearing and corrosion of this material and have performed several explorations [10,11]. Recently, Wang et al have studied the tangential fretting wear of 2.25Cr-1Mo steel and the effect of 2.25Cr-1Mo steel wear behavior at high temperatures [10,12].…”
Section: Introductionmentioning
confidence: 99%